Si Lewen's Parade : an artist's odyssey - Lewen, Si (Abrams ComicArts, 2016)
"Si Lewen's Parade is a timeless story told in a language that knows no country...a wordless epic that, despite its muteness, is more powerful than the written or the spoken word. First published in 1957, The Parade is a lost classic, newly discovered, remastered, and presented by Art Spiegelman, the Pulitzer Prize-winning author of Maus. Reproduced in a unique two-sided accordion-fold format with an extensive overview of the artist's career on the verso, The Parade is a celebration of art and the story of recurring war as Si Lewen experienced it over the past 90 years, watching the joyful parades that marked the end of World War I lead into the death marches of World War II and the Korean War. As The Parade unfolds, the reader is taken on an unforgettable journey of sequential images"...